"And Poland is filed away with Samothrace": Australian Responses to Poland's June 1956 Crisis. (25th April 2018) - Rudzinski, Adrian; Korobacz, Victor
Abstract : The suppression of Poznan June 1956 workers' rebellion ( Poznanski Czerwiec ) by Polish authorities prompted immediate Australia‐wide demonstrations and protests by Polish émigrés who were supported by friends and allies in the Catholic Church and the Australian anti‐communist movement. Nation‐wide demonstrations in Australia and subsequent approaches by émigré Poles and supporters required a disinterested Australian government to develop a position on Poznan June events. Pressure on the Australian government for a response, potentially disruptive to its foreign policies, was applied only by elements within the Australian political scene that posed little threat to its future. Poznan June '56's effect on Australia takes place within the particular nature of Australian domestic politics where the June events were used to fan the flames of bitter rivalry within the labour movement by a strident anti‐communist faction seeking to restructure the Australian Labor Party in a manner consistent with its ideological predilections. In taking up the anti‐communist cause of the Polish émigrés, the Australian anti‐communist leadership claimed a moral high‐ground, but lacked sufficient commitment to use their considerable parliamentary advantage to pressure the Australian government to adopt a more muscular position towards Poland's government.